AN AYURVEDIC PEDIATRIC CLINICAL EXAMINATION :- VEDANADHYAYA - Dr. Komal Rathore (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2018)
The field of Ayurveda is Broadly divided into eight elements. Kaumarbhritya refers to the science of diseases and care of children, right from conception till adolescence. Kashyap Vedic literature is doubtless the pioneer text throughout this branch of Ayurveda. The text is split in varied sections (Sthanas) of that Vedanadhyaya is twenty fifth chapter in Sanskrit literature sthana. It problems the symptomalogy of various diseases in children and is a superb steering for pediatric examination and identification as children area unit unable to narrate their symptoms themselves. the present article reviews the primary text of the chapter and critically analyses it in light-weight of up so far bioscience. it's noticeable that Acharya Kashyap has fenced in an outsized vary of diseases pertaining to varied systems like skin, ENT, gastro-biliary, medical science and genitourinary apparatus and has together fenced in the Bal grahas. The symptoms drawn ar correct and low-cost in up so far scientific era together. Thus, Associate in Nursing intensive study of Vedanadhyaya is crucial for proper understanding of Ayurvedic perspective of pediatric illness and their common demarcating symptoms. It reinforces the browse that youngsters do not appear to be miniature adults and diseases in pediatric population have distinct choices and wish to be understood on a personal basis. Keyword:-Kashyapa Samhita, Pediatric Clinical Examination, Vedanadhyaya.